FUNDAMENTAL STUDIES IN BASIC AND CLINICAL IMMUNOLOGY PERFORMED BY ACADEMICIAN V.I. IOFFE (TO THE 120th ANNIVERSARY OF THE BIRTH OF ACADEMICIAN V.I. IOFFE) - P. G. Nazarov (SPb RAACI, 2018)
In 2018, we celebrate the 120th anniversary of Academician, Professor Vladimir I Ioffe, a leading figure of national immunology. The world-level achievements of V.I.Ioffe in research, his undisputed priority in the most important areas of fundamental immunology are worth of recognition and interest among the immunologists. V.I.Ioffe was far-seeing and precise in his scientific prescience. He has authored a number of discoveries which were proved to be of fundamental and practical significance over 50 succeeding years. The scientific contribution of V.I.Ioffe is considered equal to achievements of the most illustrious Nobel Prize winners. Academician V.I.Ioffe regarded the immune pathology as a next step in development of general immunology, thus allowing applications of general fundamental immunology to the tasks of immune pathology. Vladimir I. Ioffe is rightly seen as a founder of native clinical immunology. He has formulated the tasks of clinical immunology as based on interests and requirements of clinicians.  Vladimir I.Ioffe has presented a condition which he related to any study in clinical immunology, i.e., a need for comparisons between the results of immunological testing and clinical course of the disease. All the requirements in immune laboratory diagnostics, having been proposed and established by the Academician Vladimir I. Ioffe, have kept their significance up to the present day.